The Cajal Body Protein WRAP53β Prepares the Scene for Repair of DNA Double-Strand Breaks by Regulating Local Ubiquitination - Bergstrand, Sofie; O'Brien, Eleanor M.; Farnebo, Marianne (Frontiers in Molecular Biosciences, 2019)
Proper repair of DNA double-strand breaks (DSBs) is critical for maintaining genome integrity and avoiding disease. Modification of damaged chromatin has profound consequences for the initial signaling and regulation of repair. One such modification involves ubiquitination by E3 ligases RNF8 and RNF168 within minutes after DSB formation, altering chromatin structure and recruiting factors such as 53BP1 and BRCA1 for repair via non-homologous end-joining (NHEJ) and homologous recombination (HR), respectively. The WD40 protein WRAP53β plays an essential role in localizing RNF8 to DSBs by scaffolding its interaction with the upstream factor MDC1. Loss of WRAP53β impairs ubiquitination at DNA lesions and reduces downstream repair by both NHEJ and HR. Intriguingly, WRAP53β depletion attenuates DSB repair more than depletion of RNF8, indicating functions other than RNF8-mediated ubiquitination. WRAP53β plays key roles with respect to the nuclear organelles Cajal bodies, including organizing the genome to promote associated transcription and collecting factors involved in maturation of the spliceosome and telomere elongation within these organelles. It is possible that similar functions may aid also in DSB repair. Here we describe the involvement of WRAP53β in Cajal bodies and DSB repair in detail and explore whether and how these processes may be linked. We also discuss the possibility that the overexpression of WRAP53β detected in several cancer types may reflect its normal participation in the DNA damage response rather than oncogenic properties.